The New Testament speaks ; v. 3 explaining the New Testament as it was understood by its first readers - Fleming, Donald C. (Manila, Philippines Living Books for All, 1975)
Contents : v. 3 : Romans - Corinthians.
Brethren writer. Donated by the author.
Keywords: Bible. N.T. -- introductions